Location of Decision Rights in Catholic Religious Orders. (8th November 2012) - Ehrmann, Thomas; Rost, Katja; Inauen, Emil
<x xml:space="preserve">Abstract</x> Organizational incentives are an important part of applied economics. Do even organizations like religious orders make the same trade‐offs and substitutions as predicted by economics for firms? It is argued here that religious orders face the problem of controlling the actions of their branch offices to assure the continued value and uniqueness of their trademark. We use the distinction between specific and general knowledge to analyze the optimal colocation of decision rights within the specific knowledge framework of a religious order. Assuming that knowledge is valuable in decision making, then the colocation of the decision authority with the particular knowledge that is beneficial to those decisions is preferable. With a sample of 114 local communities of 20 religious orders of the Roman Catholic Church, we empirically test whether the ratio of search/experience goods, of credence goods and the monitoring costs of the headquarter can explain the colocation of decision rights and authority within an order. Our findings give support for the hypothesis that religious orders at present make the same trade‐offs and substitutions as predicted by economics. Copyright © 2012 John Wiley & Sons, Ltd.